Studies on electrodeposition behavior of Sn–Bi alloys in plating baths modified by hydroquinone and gelatin - Goh, Y.; Haseeb, A.S. Md. Abdul (Kluwer (now part of Springer), 2016)
This work focuses on the investigation of the electrochemical behavior of Sn–Bi plating bath modified by two electrolyte additives, hydroquinone (HQ) and gelatin. Electrochemical studies were carried out by low sweep rate polarization scans, as well as cyclic voltammetry at different scan rates (1–40 mV/s). Polarization scans at sweep rate of 1 mV/s indicate that Bi deposits at about −25 to −45 mV while Sn deposits at about −410 to −420 mV in the plating bath without additives or with either one of the additives. The addition of HQ suppresses hydrogen evolution to more electronegative potentials, showing its adsorption capabilities. On the other hand, gelatin shifts the deposition potential of Bi and is suggested to have a mild complexing effect with Bi ions. The synergistic effect of both HQ and gelatin reduces the potential gap between Bi and Sn from 429 to 255 mV. Investigations on single metallic Sn and Bi plating baths at varying sweep rates reveal different behavior of Sn and Bi ions. The shifting and broadening of Bi cathodic peak potential upon HQ + gelatin addition suggest the formation of HQ–gelatin complex species. Surface morphology and composition analyses were conducted on electrodeposits from each plating bath. Near-eutectic Sn–Bi alloy was successfully electrodeposited from the plating bath modified by HQ + gelatin.